Creative Teaching With Google Classroom For Teachers Of 096 Manyabar State Elementary Schools - Guntur Maha Putra; Nurul Atikah; Rizky Putri Mahfuz; Dessy Rahmadhani; Selma Karamy Zulpana Tanjung; Putri Anggina (STMIK Royal, 2022)
Abstract: This Community Service activity was carried out at SD Negeri 096 Manyabar, Panyabungan District, Mandailing Natal Regency, North Sumatra. This activity is carried out with the aim of helping adapt technology that is in line with the MBKM (Merdeka Belajar – Kampus Merdeka) program, one of which is the use of the google classroom platform in the process of e-learning teaching and learning activities in schools to create creative, interactive, effective and efficient learning between teachers and students, especially during this Covid-19 pandemic. Google classroom is a free, web-based platform built to make it easier for educators and students to learn online, which is easy to use to help teachers manage, measure, and experiential learning. The current use of Google Classroom is very efficient which is not limited by effective space and time. Teachers can provide online material, either in the form of text, images, audio, or video to students, besides that teachers can also make quizzes, assignments, and student lists on a regular basis by using a link from the google form sent to google classroom. Online learning in this Covid-19 era makes learning activities can be carried out interactively, effectively, and efficiently between teachers and students by utilizing technology, one of which is the use of the google classroom platform. Keywords: google classroom; online learning; e-learning Abstrak: Kegiatan Pengabdian Masyarakat ini dilaksanakan di SD Negeri 096 Manyabar, Kecamatan Panyabungan, Kabupaten Mandailing Natal, Sumatera Utara. Kegiatan ini dilaksanakan bertujuan dalam hal membantu adaptasi teknologi yang selaras dengan program MBKM (Merdeka Belajar – Kampus Merdeka) yang salah satunya adalah dengan pemanfaatan plafform google classroom dalam proses kegiatan belajar mengajar e-learning di sekolah untuk menciptakan pembelajaran kreatif, interaktif, efektif dan efisien antara guru dengan siswa apalagi dimasa pandemi Covid-19 ini. Google classroom adalah platform gratis berbasis web yang dibuat untuk mempermudah kegiatan pembelajaran pendidik dan siswa secara online yang mudah digunakan untuk membantu pengajar mengelola, mengukur, dan memperkaya pengalaman belajar. Pemanfaatan Google classroom saat ini sangat efektif dan efisien yang tidak terbatas oleh ruang dan waktu. Guru dapat memberikan materi secara online, baik berupa teks, gambar, audio, maupun video kepada peserta didik, selain itu guru juga dapat membuat kuis, tugas maupun daftar kehadiran siswa secara berkala dengan menggunakan link dari google form yang dikirimkan ke google classroom. Pembelajaran secara daring dimasa Covid-19 ini membuat kegiatan belajar dapat dilakukan secara interaktif, efektif dan efisien antara guru dengan siswa dengan pemanfaatan teknologi salah satu dengan pemanfaatan plafform google classroom.Kata kunci: google classroom; pembelajaran daring; e-learning